Moral power : the magic of witchcraft - Stroeken, Koen (Epistemologies of healing, 2010)
Neither power nor morality but both. Moral power is what Sukuma farmers in Tanzania in times of crisis attribute to an unknown figure they call their witch. A universal process is involved, as much bodily as social, which obstructs the patient's recovery. Healers turn the table on the witch through rituals showing that the community and the ancestral spirits side with the victim. In contrast to biomedicine, their magic and divination introduce moral values that assess the state of the system and that remove the obstacles to what is taken as key: self-healing. The implied 'sensory shifts' and therapeutic effectiveness have largely eluded the literature on witchcraft. This book shows how to comprehend culture other than through the prism of identity politics. It offers a framework to comprehend the rise of witch killings and human sacrifice, just as ritual initiation disappears